2021
DOI: 10.3390/ani11020493
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Resulting from Undesirable Behaviours in Dogs Aged Three Years and under Attending Primary-Care Veterinary Practices in Australia

Abstract: There is increasing evidence that undesirable behaviours (UBs) in dogs can compromise the welfare of both canine companions and their carers. Veterinarians are regularly consulted about affected animals and may be asked to euthanase the more severely affected individuals. A recent study of veterinary records showed that UBs were the predominant cause of mortality in young dogs in the UK. This companion study from Australia reports the proportion of mortality due to UBs among dogs aged three years and under tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 65 publications
(124 reference statements)
2
11
0
Order By: Relevance
“…As aggression is an UB that can be highly hazardous to humans [ 64 ], it may have led to some dogs being euthanased or relinquished before drug therapy could be trialled. This is supported by previous epidemiological studies of causes of mortality in dogs aged three years and under, which revealed that 33.7% of dogs in the UK [ 11 ] and 29.7% in Australia [ 25 ] had UBs, with the most common UB reported as a cause of death being aggression (54% in England and 52.5% in Australia). Furthermore, within these studies, pharmaceutical, pheromone or nutraceutical treatments for aggression were attempted in just 3% of the UK sample [ 11 ] and 5.9% of the Australian sample [ 25 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…As aggression is an UB that can be highly hazardous to humans [ 64 ], it may have led to some dogs being euthanased or relinquished before drug therapy could be trialled. This is supported by previous epidemiological studies of causes of mortality in dogs aged three years and under, which revealed that 33.7% of dogs in the UK [ 11 ] and 29.7% in Australia [ 25 ] had UBs, with the most common UB reported as a cause of death being aggression (54% in England and 52.5% in Australia). Furthermore, within these studies, pharmaceutical, pheromone or nutraceutical treatments for aggression were attempted in just 3% of the UK sample [ 11 ] and 5.9% of the Australian sample [ 25 ].…”
Section: Discussionsupporting
confidence: 77%
“…One study reported that 33.7% of dogs died as a result of an UB (including road traffic accidents (RTAs), as RTAs may result from poor recall, limited traffic training or straying) [ 11 ], where another study reported 14.7% of deaths ascribed to behavioural abnormality and a further 12.7% ascribed to RTAs (a combined total of 27.4%) [ 24 ]. Comparable findings using a similar study design have recently emerged from Australia (29.7%) [ 25 ].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Prior to the pandemic, SRBs had been reported to affect up to 50% of dogs in the UK [ 13 ] but this may even be an underestimate as, by definition, SRBs are demonstrated during the owner’s absence and therefore may not be noticed by the owner. In summary, the early-life experiences of Pandemic Puppies could put this cohort at greater risk of future behavioural issues, which may in turn increase their risk of later relinquishment or euthanasia, given that undesirable behaviours are one of the main drivers for relinquishment [ 14 ] and euthanasia of dogs under the age of three years [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Canine behavior problems can often be indicative of a poor welfare state (4,5) and lead to an increased risk of euthanasia. Undesirable behavior is the leading cause of mortality among privately owned dogs under the age of 3 years (6,7). Problem behaviors have also been associated with reduced owner attachment and satisfaction (8)(9)(10)(11) which may threaten the human-animal bond and place the dog at increased risk of relinquishment as behavioral issues are a leading cause of canine relinquishment worldwide (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%